P-088 Diabetic Nephropathy and IgA Nephropathy are the Most Prevalent Nephrotic/Nephritic Disease in Inflammatory Bowel Disease. (February 2017) - Sharma, Prabin; Aguilar, Rodrigo; Mordon, Armenia; Chedid, Alice; Tabanor, Joy-Ann; Montero, Alex; Shammash, Jonathan; Asif Siddiqui, Omer; Li, Ping; Abi Nader, Mark
Abstract : Background: Various renal diseases and renal complications have been associated with Inflammatory Bowel Disease (IBD), which include nephrolithiasis, amyloidosis, interstitial nephritis, and glomerulonephritis (GN). Medications used in IBD treatment such as Aminosalicylates, cyclosporine and Tumor Necrosis Factor-Alpha inhibitors have also been implicated in renal diseases in these patients. Nephrotic and Nephritic syndromes have been reported in patients with IBD but the epidemiology remains poorly understood. The aim of this study is to evaluate the epidemiology of nephrotic and nephritic syndromes in patients with Crohn's Disease (CD) and Ulcerative colitis (UC). Methods: Between 2004 and 2012, we used the Nationwide Inpatient Sample Database to identify patients with Inflammatory Bowel disease (ICD 9 Codes 555.0, 555.1, 555.2, 555.9, 556.0, 556.1, 556.3, 556.4, 556.5, 556.6, 556.8, 556.9), Nephrotic Syndrome (ICD 9 Codes 581.0, 581.1, 581.2, 581.3, 577.3, 250.40, 250.41, 250.42, 250.43) and Nephritic Syndrome (ICD 9 Codes 580.0, 580.4, 583.81, 446.21, 583.9, 759.89, 446.4, 446.21, 583.89, 287.0, 584.7, 446.6, 759.89). Patients with CD were compared with those with UC for each type of nephrotic and nephritic syndrome. All categorical variables were compared with Pearson's χ 2 test and continuous variables were analysed with paired t test. Analyses were performed using SAS version 9.3 (SAS Institute). Results: Between 2004 and 2012, we identified 268, 170 patients with CD and 152, 804 patients with UC admitted to the hospital. Nephrotic and Nephritic diseases were rarely associated with these IBD patients; prevalence ranging from 0.001% to 0.05%. Diabetic nephropathy was the nephrotic disease with the highest prevalence in both CD (0.16%, n = 416) and UC (0.27%, n = 419) followed by renal amyloidosis (0.02%, n = 44 and 0.02%, n = 25). Similarly, IgA Nephropathy was the leading cause of glomerulonephritis in both CD (0.02%, n = 127) and UC (0.02%, n = 80) followed by renal diseases associated with thin basement membrane disease (0.04%, n = 94 versus 0.03%, n = 39), Granulomatous with polyangitis (0.01%, n = 66 versus 0.04%, n = 63), Thrombotic Microangiopathy (0.01%, n = 32 versus 0.02%, n = 33), Henoch schonlein purpura (0.01%, n = 32 versus 0.01%, n = 20) and Alport Syndrome (0.01%, n = 30 versus 0.02%, n = 24). Other renal diseases such as Goodpasture syndrome (0.002%, n = 5 versus 0.002%, n = 6), Mimimal change disease (0.003%, n = 7 versus 0.003%, n = 5), Focal Segmental Glomerulosclerosis (0.001%, n = 4 versus 0.003%, n = 8), Proliferative GN (0.001%, n = 2 versus 0.001%, n = 1), Rapidly progressive GN (0.001%, n = 2 versus 0.001%, n = 1), Membranoproliferative GN (0.001%, n = 2 versus 0%, n = 0) and Analgesic nephropathy (0%, n = 0 versus 0.001%, n = 1) were less commonly encountered. Conclusions: Nephrotic and Nephritic syndromes are uncommonly associated with IBD patients. However, when a patient with CD or UC presents with proteinuria or hematuria, Diabetic nephropathy and IgA nephropathy should be high on the differential.